TCP Transcription Factors Involved in Shoot Development of Ma Bamboo (Dendrocalamus latiflorus Munro) - Jin, Kangming; Wang, Yujun; Zhuo, Renying; Xu, Jing; Lu, Zhuchou; Fan, Huijin; Huang, Biyun; Qiao, Guirong (Frontiers in Plant Science, 2022)
Ma bamboo (Dendrocalamus latiflorus Munro) is the most widely cultivated clumping bamboo in Southern China, and is valuable for both consumption and wood production. The development of bamboo shoots involving the occurrence of lateral buds is unique, and it affects both shoot yield and the resulting timber. Plant-specific TCP transcription factors involved in plant growth and development, particularly in lateral bud outgrowth and morphogenesis. However, the comprehensive information of the TCP genes in ma bamboo remain poorly understood. In this study, 66 TCP transcription factors were identified in ma bamboo at the genome-wide level. Members of the same subfamily had conservative gene structures and conserved motifs. Collinear analysis demonstrated that segmental duplication occurred widely in the TCP transcription factors of ma bamboo, which mainly led to the expansion of gene family. Cis-acting elements related to growth and development and stress response were found in the promoter regions of DlTCPs. Expression patterns revealed that DlTCPs have tissue expression specificity, which is usually highly expressed in shoots and leaves. Subcellular localization and transcriptional self-activation experiments demonstrated that the five candidate TCP proteins were typical self-activating nuclear-localized transcription factors. Additionally, the transcriptome analysis of the bamboo shoot buds at different developmental stages helped clarify the underlying functions of the TCP members during the growth of bamboo shoots. DlTCP12-C, significantly down-regulated as the bamboo shoots developed, was selected to further verify its molecular function in Arabidopsis. The DlTCP12-C overexpressing lines exhibited a marked reduction in the number of rosettes and branches compared with the wild type in Arabidopsis, suggesting that DlTCP12-C conservatively inhibits lateral bud outgrowth and branching in plants. This study provides useful insights into the evolutionary patterns and molecular functions of the TCP transcription factors in ma bamboo, and provides a valuable reference for further research on the regulatory mechanism of bamboo shoot development and lateral bud growth.